DOES TECHNOLOGY USE PROTECT AGAINST COGNITIVE DECLINE? RESULTS FROM A RETROSPECTIVE COHORT STUDY. (11th November 2018) - Harris, D; Thomas, K; Jutkowitz, E
Abstract: Technology use among older adults is increasing rapidly. Cross-sectional studies have identified an association between technology use and better cognitive performance among older adults; however, to our knowledge, no studies have longitudinally investigated this relationship. To address this gap, we used data from the National Health and Aging Trends Study, a nationally representative cohort of Medicare-eligible older adults from 2011–2014 (N=8, 245). Technology users were defined as having emailed or texted within the last 30-days of their baseline assessment. Cognitive performance was assessed at each wave using the delayed word recall test. Cognitively intact community-dwelling participants with valid data for technology use and delayed word recall at baseline were included in the analysis (n=5, 208). We estimated a linear mixed-effect regression to examine the association between baseline technology use and cognitive performance over time. We adjusted for baseline cognitive performance, demographic and socioeconomic characteristics, the assessment wave, and an interaction between technology use and wave. At baseline, 55% identified as female, 52% were above 75 years old and 53% had a college education. Delayed recall scores among technology users were higher than non-technology users (Mean=4.1, SE=0.04 vs. Mean=3.0, SE=0.03) at baseline. Adjusted regression results showed that baseline technology use was associated with 0.24-point (95%CI:0.14–0.35) higher delayed word recall score and a 0.05 point (95%CI:0.01–0.09) increase in delayed word recall over time, compared to non-technology users. These results add to a growing body of literature highlighting the potentially protective effects of technology on cognition in older adults.